2017
DOI: 10.1002/ejp.1096
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for the prevention of low back and pelvic girdle pain in pregnancy: A meta‐analysis of randomized controlled trials

Abstract: Background and objective: The effect of exercise in prevention of low back and pelvic girdle pain during pregnancy is uncertain. This study aimed to assess the effect of exercise on low back pain, pelvic girdle pain and associated sick leave. Databases and data treatment: Literature searches were conducted in PubMed, EMBASE, Cochrane Library, Google Scholar, ResearchGate and ClinicalTrials.gov databases from their inception through May 2017. Randomized controlled trials (RCTs) were eligible for inclusion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 38 publications
(90 reference statements)
2
61
1
6
Order By: Relevance
“…Hence, exercise, a powerful mechanism to improve PF, could be effective in the prevention of low-back pain during pregnancy, reducing its intensity and associated disability, and sick leaves. 13,28 We have confirmed that greater overall PF is associated with less pain disability due to lumbar and sciatic pain, assessed by the ODI questionnaire, although lower pain intensity was not associated with greater overall PF.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, exercise, a powerful mechanism to improve PF, could be effective in the prevention of low-back pain during pregnancy, reducing its intensity and associated disability, and sick leaves. 13,28 We have confirmed that greater overall PF is associated with less pain disability due to lumbar and sciatic pain, assessed by the ODI questionnaire, although lower pain intensity was not associated with greater overall PF.…”
Section: Discussionsupporting
confidence: 58%
“…Another meta-analysis found that even during and after pregnancy, osteopathic manipulative treatment for low back and pelvic girdle pain during and after pregnancy gave clinically relevant benefits [ 37 ]. A meta-analysis of randomized controlled trials (RCTs) published in 2018 showed that exercise decreased the risk of low back pain in pregnancy by 9% [pooled risk ratio (RR) = 0.91; 95% CI 0.83–0.99; I 2 = 0%, seven trials; n = 1175] [ 38 ]. However, there was no protective effect on pelvic girdle pain (RR = 0.99; CI 0.81–1.21; I 2 = 0%; four RCTs; n = 565), or on lumbar- pelvic pain (RR = 0.96; CI 0.90–1.02; I 2 = 0%; eight RCTs; n = 1737) [ 38 ].…”
Section: Pregnancymentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials (RCTs) published in 2018 showed that exercise decreased the risk of low back pain in pregnancy by 9% [pooled risk ratio (RR) = 0.91; 95% CI 0.83–0.99; I 2 = 0%, seven trials; n = 1175] [ 38 ]. However, there was no protective effect on pelvic girdle pain (RR = 0.99; CI 0.81–1.21; I 2 = 0%; four RCTs; n = 565), or on lumbar- pelvic pain (RR = 0.96; CI 0.90–1.02; I 2 = 0%; eight RCTs; n = 1737) [ 38 ]. In lumbar-pelvic pain, exercise was able to prevent new episodes of sick leave (RR = 0.79; CI 0.64–0.99; I 2 = 0%; three RCTs; n = 1168) [ 38 ].…”
Section: Pregnancymentioning
confidence: 99%
“…The clinical efficacy of exercise therapy for preventing low back pain in pregnancy has been reported recently (Shiri et al, 2018). Exercise also alleviates stress and depression that are often associated with chronic pain conditions (Sigwalt et al, 2011;Lima et al, 2017).…”
Section: Introductionmentioning
confidence: 99%